THE RELATIONSHIP BETWEEN THE CLASSIFICATION OF HEART FAILURE PATIENTS WITH RENAL CREATININE UREA LEVELS IN TULIP IIC ULIN PUBLIC HOSPITAL BANJARMASIN - Bagus Rahmat Santoso; Eirene Eunike Meidiana Gaghauna (Universitas Sari Mulia, 2015)
Background : Classification of heart failure is a stage heart failure based on signs and symptomscaused. Most patients with low of Glomerular Filtration Rate (GFR) is also in a lower NYHAfunctional class. Increasing concentrations of substances urea and creatinine is proportional to thenumber of functional nephron reduction, so it is an important tool to assess the degree of renalfailure.Methods : This study used a cross-sectional approach. Research sampling technique used in thisresearch is purposive sampling with the number of sample is 56 samples. Data were collected byusing a check list. Data were analyzed using Chi Square with significant value of p 0.05.Result : Results showed respondents with lower levels of urea + normal were 38 respondents(67.9%) and high urea levels as much as 18 respondents (32.1%). Based on the results of thebivariate analysis using Chi-square test p = 0.490 obtained because p 0.05 (0.490 0.05), it can bestated there was no relationship between heart failure class with urea in Tulip IIC Ulin PublicHospital Banjarmasin. And the results showed respondents with low creatinine levels were 38normal + respondents (67.9%) and creatinine levels were higher by 18 respondents (32.1%). Basedon the results of the bivariate analysis using Chi-square test p = 0.421 obtained because p 0.05(0.421 0.05), it can be stated there was no relationship between the classes of heart failure withcreatinine levels in Space Tulip IIC Ulin Public Hospital Banjarmasin.Conclusion : Results of the analysis showed that there is no relationship between the classificationof heart failure patients with renal creatinine urea levels in tulip IIC Ulin Public HospitalBanjarmasin.Keywords: Classification of Heart Failure, Urea, Creatinine